Generalized derivatives of computer programs. (4th March 2022) - Billingsley, Matthew R.; Barton, Paul I.
ABSTRACT: A method for evaluating lexicographical directional (LD)-derivatives of functional programs is presented, extending previous methods to programs containing conditional branches and loops. A language for imperative programs is given, and conditions under which LD-derivatives can be calculated automatically for conditional branches and loops are described, along with a full description of the source transformation procedures necessary.